2009
DOI: 10.1530/rep-09-0163
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of meiosis associated SYCP family members during germline development in chickens

Abstract: Synaptonemal complexes (SCs) are associated with synapsis of homologous chromosomes, chiasmata distribution, recombination and segregation of chromosomes during the extended prophase of meiosis I. Three isoforms of SC proteins, SYCP1, SYCP2 and SYCP3, were identified as the structural proteins of SCs, and may be involved in the assembly and disassembly of SCs. The aim of this present study is to determine the pattern of expression of chicken homologues of SYCP family members during ovarian and testicular devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…In agreement with these data from classical histological sections, the SC protein SYCP3 is first detectable by immunofluorescence on E15.5 in female chicken gonads [Smith et al, 2008;Zheng et al, 2009]. The only quantitative analysis of chicken oogenesis was performed using histological sections of chicken ovaries from E15 to the day of hatching [Hughes, 1963].…”
mentioning
confidence: 74%
“…In agreement with these data from classical histological sections, the SC protein SYCP3 is first detectable by immunofluorescence on E15.5 in female chicken gonads [Smith et al, 2008;Zheng et al, 2009]. The only quantitative analysis of chicken oogenesis was performed using histological sections of chicken ovaries from E15 to the day of hatching [Hughes, 1963].…”
mentioning
confidence: 74%
“…1 b, c). Subsequently, sequence alignment and expression analyses showed that the 3 major SC proteins SYCP1, SYCP2, and SYCP3 share basic structural features in birds and mammals and are present in chicken gonads at the moment of meiosis [Zheng et al, 2009]. The percentage identity between chicken and mammalian SYCP proteins over the entire alignment indicates different levels of conservation, with the highest similarity for SYCP3 [Zheng et al, 2009].…”
Section: The Organization Of Bivalents During the Meiotic Prophasementioning
confidence: 99%
“…Subsequently, sequence alignment and expression analyses showed that the 3 major SC proteins SYCP1, SYCP2, and SYCP3 share basic structural features in birds and mammals and are present in chicken gonads at the moment of meiosis [Zheng et al, 2009]. The percentage identity between chicken and mammalian SYCP proteins over the entire alignment indicates different levels of conservation, with the highest similarity for SYCP3 [Zheng et al, 2009]. In addition to specific SC proteins, the cohesin component SMC3 is also present on the meiotic axes of chickens and other birds from leptotene to late diplotene [Pigozzi, 2008;del Priore and Pigozzi, 2012] and is a component of the chromatin axes of lampbrush bivalents in the period of pre-vitellogenesis [Krasikova et al, 2005].…”
Section: The Organization Of Bivalents During the Meiotic Prophasementioning
confidence: 99%
“…Furthermore, the evolutionary relationship between NO145 and SYCP2 opened additional questions about a potential last common ancestor of both proteins and the point of their separation. It was of avail that the chicken SYCP2 was characterized as the only non-mammalian orthologue just a few years ago (Zheng et al 2009). …”
Section: Introductionmentioning
confidence: 99%